Investigation On Mdof Bilateral Teleoperation Control System Using Geared Dc-Motor - Lee, Jun Wei; Shukor, Ahmad Zaki; Jamaluddin, Muhammad Herman (Canadian Center of Science and Education, 2016)
This paper presents the research on bilateral teleoperation control system of two link planar manipulator. The bilateral control system consists of master and slave system using geared DC-motor. Both master and slave manipulators are actuated by DC-Micromotor attached to planetary gearhead to increase the output torque. In the previous researches, the common used actuators were linear motors and direct drive DC motor. However, the application of DC motor with gearhead is vast in industry, due to the need for high output force or torque. Thus in this paper, a deeper research on bilateral teleoperation control system is proposed with implementation of gear into the DC-motor. The modelling of multi-degrees-of-freedom (MDOF) bilateral teleoperation control system is designed with the implementation of workspace observer (WOB), reaction force observer (RFOB), position controller and force controller. During the experiments, free motion and contact motion were conducted to validate the proposed setup in bilateral teleoperation control system. The position and torque responses of both master and slave manipulators were observed. The operationality and reproducibility of this proposed system were evaluated through experimental results. Ultimately, this paper focused on the performance of the proposed setup and is analysed by using reproducibility and operationality.